2021
DOI: 10.1094/mpmi-09-20-0256-r
|View full text |Cite
|
Sign up to set email alerts
|

Ralstonia solanacearum Type III Effector RipJ Triggers Bacterial Wilt Resistance in Solanum pimpinellifolium

Abstract: Ralstonia solanacearum causes bacterial wilt disease in solanaceous crops. Identification of avirulence type III secreted effectors recognized by specific disease resistance proteins in host plant species is an important step towards developing durable resistance in crops. In the present study, we show that R. solanacearum effector RipJ functions as an avirulence determinant in Solanum pimpinellifolium LA2093. 10 candidate avirulence effectors were shortlisted based on the effector repertoire comparison betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…Some T3Es with important functions are selected out largely depending on the comparative analysis of the effectors. For instance, the recently reported R. solanacearum avirulence effectors RipJ and RipAZ1 are identified by the comparative genomic analysis of two strains with different virulence against S. pimpinellifolium and S. americanum , respectively ( Moon et al, 2021 ; Pandey and Moon, 2021 ). Similarly, by comparing all the effectors of PeaFJ1 and HA4-1, we found that most of the effectors are exactly identical with the counterparts of R. solanacearum HA4-1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some T3Es with important functions are selected out largely depending on the comparative analysis of the effectors. For instance, the recently reported R. solanacearum avirulence effectors RipJ and RipAZ1 are identified by the comparative genomic analysis of two strains with different virulence against S. pimpinellifolium and S. americanum , respectively ( Moon et al, 2021 ; Pandey and Moon, 2021 ). Similarly, by comparing all the effectors of PeaFJ1 and HA4-1, we found that most of the effectors are exactly identical with the counterparts of R. solanacearum HA4-1.…”
Section: Resultsmentioning
confidence: 99%
“…The research revealed that IPO1609 carries a 77 kb genomic deletion, which is responsible for almost complete loss of pathogenicity of the strain ( Gonzalez et al, 2011 ). Recently, the R. solanacearum avirulence effectors RipJ and RipAZ1 were identified by the comparative genomic analysis of two strains with different virulence against Solanum pimpinellifolium and S. Americanum , respectively ( Moon et al, 2021 ; Pandey and Moon, 2021 ). In the current study, we performed a comprehensive comparative analysis of the genome sequences of R. solanacearum strain PeaFJ1 and other strains, especially HA4-1.…”
Section: Introductionmentioning
confidence: 99%
“…The effector proteins of R. solanacearum have functional redundancy, and many effector proteins are also recognized by host immunity (Landry et al 2020 ). It is noteworthy that since RipJ belongs to the well-known YopJ family of acetyltransferases but is an avirulence protein that triggers bacterial wilt resistance in Solanum pimpinellifolium (Pandey et al 2021 ). These results suggest that the role of these effectors in strain SY1 infection may be amplified or negligible during the infection of some specific host plants.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding effector types, some are defense-related avirulence effectors that induce ETI in the presence of a resistance protein, e.g., RipB [ 103 ] and RipJ [ 104 ], while other bacterial T3Es can suppress ETI and PTI-associated cell death caused by other effectors and elicitors. For example, AvrRpt2 suppresses ETI cell death caused by the effector HopA1, and HopF2 suppresses flagellin-induced PTI [ 135 ].…”
Section: Effectors and Plant Defensementioning
confidence: 99%